ETHNOBOTANICAL STUDY OF MEDICINAL PLANT USAGE DURING COVID-19 PANDEMIC: A COMMUNITY-BASED SURVEY IN INDONESIA - Nayaka, Ni Made Dwi Mara Widyani; Yuda, Putu Era Sandhi Kusuma; Sanjaya, Dwi Arymbhi; Ernawati, Desak Ketut; Cahyaningsih, Erna; Dewi, Ni Luh Kade Arman Anita; Sasadara, Maria Malida Vernandes (BIOTROPIA, 2023)
Before the availability of a vaccine, Indonesian population relied on traditional medicines to prevent COVID-19. Any species used by indigenous people could lead to further investigations in modern pharmacology, to preserve ancient knowledge, and to plan for plants’ conservation. The study aimed to discover and record species, methods of preparation, route of administration, and motivation in using medicinal plants by the Indonesian population during the COVID-19 pandemic. Participants of survey were selected from the people who live in Java and Bali for responding to an online structured questionnaire. Relative Frequency of Citation (RFC) was employed in the quantitative analysis of the collected data. The pharmacological relevance of the five plants with the highest RFC was further reviewed. The results showed that respondents used 59 plants from 28 families. Five species with the highest RFC were Curcuma longa (0.707), Zingiber officinale (0.674), Cymbopogon citratus (0.269), Kaempferia galanga (0.174), and Curcuma zanthorrhiza (0.165). Most plants were prepared by boiling (77.97%) and administered orally as a single ingredient or mixed with other herbals. Respondents believed that the plants were beneficial as immune-booster (71.26%), maintain good health (24.85%) and stamina (12.28%), and prevent viral infection, including COVID-19 (5.39%). The most commonly used plants might be scientifically based to boost immunity. However, their usage against COVID-19 and the medicinal value of herbal mixtures should be further investigated.